PERUBAHAN KONTRIBUSI USAHATANI JARAK PAGAR PADA PENDAPATAN RUMAH TANGGA PETANI DI KECAMATAN SAPTOSARI KABUPATEN GUNUNGKIDUL - , BAKDIYATI, Prof. Dr. Ir. Irham, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to (1) Know the jatropha curcas farming expedience (2) To see changes jatropha curcas farming contribution to the income of farmersâ households (3) To analyze poverty level jatropha curcas farmersâ households. The basic method of this research were descriptive analysis, respondent determination were determined by snowball sampling that were subsequent sampling based on information from the previous farmer sample which consisting of 30 jatropha curcas farmers in the Kanigoro Village and Monggol Saptosari Sub-district. Data analysis were done by table analysis, contribution percentage, and poverty indicator. Result of the analysis shows that (1) Jatropha curcas farming were still worth to organised and developed with more intensive crop maintenance, however in it was development, it qualification were decreasing (2) Jatropha curcas farming given small contribution to the income of farmer and there were a huge decrease in contributions due to the close cooperative agribusiness and farmers can not sell it was own jatropha curcas, so some farmers cutting down some plant jatropha curcas (3) Considered from several poverty criteria therefore (a) Farmersâ household were not considered less fortunate based on poverty criteria of Sayogyo and BPS (Central Bureau of Statistics) Gunungkidul District 2012 (b) Farmersâ households were considered less fortunate based on World Bank Criteria and FAO (Food and Agriculture Organization).